2019
DOI: 10.3390/molecules24152781
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Transformation and Enzyme Activities of Hainan Vanilla Beans During Curing to Improve Flavor Formation

Abstract: This paper compares the differences in metabolites of vanilla beans at five different curing stages. Key vanilla flavors, vanillin precursors and main enzymes during the curing process of Hainan vanilla beans were also analyzed. Hundreds of metabolites were detected based on metabolic analyses of a widely targeted metabolome technique, compared with blanched vanilla beans (BVB), sweating vanilla beans (SVB) and drying vanilla beans (DVB), the total peak intensity of cured vanilla beans (CVB) is on the rise. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
0
0
1
Order By: Relevance
“…The reduction in the PPO activity could be related to the decrease in the water content and water activity with the progress of the curing cycles. In other works, it has been reported that after blanching at 70 • C/5 min, the beans retained less than 50% of the initial PPO activity of the untreated green beans, and after 36 sunny days they showed more than 80% of the initial PPO activity [1]. Discrepancies with this work could be attributed to the differences in the curing process and vanilla variety.…”
Section: Polyphenol Oxidase (Ppo) and Peroxidase (Pod) Activitycontrasting
confidence: 85%
See 3 more Smart Citations
“…The reduction in the PPO activity could be related to the decrease in the water content and water activity with the progress of the curing cycles. In other works, it has been reported that after blanching at 70 • C/5 min, the beans retained less than 50% of the initial PPO activity of the untreated green beans, and after 36 sunny days they showed more than 80% of the initial PPO activity [1]. Discrepancies with this work could be attributed to the differences in the curing process and vanilla variety.…”
Section: Polyphenol Oxidase (Ppo) and Peroxidase (Pod) Activitycontrasting
confidence: 85%
“…During the curing of flavorless green vanilla beans, a complex mixture of more than 200 components is produced, and the beans acquire a dark brown color. Among them, vanillin (4-hydroxy-3-methoxybenzaldehyde) is the main compound responsible for flavor [1]. The curing of vanilla beans is a long, traditional, and uncontrolled process that involves four stages: killing, sweating, sun drying, and conditioning [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esto es debido a la ausencia de diversidad genética que permita aumentar la probabilidad de supervivencia con la presencia de genes que respondan de manera favorable a situaciones de estrés que afecte a las plantas morfo-fisiológicamente, derivando en problemas como aborción floral y/o de frutos, cierre estomático, reducción de la tasa fotosintética, inhibición del crecimiento, reducción del área foliar, deshidratación severa, aumento en la susceptibilidad de patógenos y por último necrosis (Borbolla-Pérez et al, 2016). Existen opciones que permiten mejorar la cadena de suministro, por ejemplo, a través del fitomejoramiento (potenciado el aroma y sabor, tamaño y grosor de las vainas, así como la resistencia a Fusarium oxysporum) (Cai et al, 2019;Pérez-Silva et al, 2021;Serrano-Fuentes et al, 2022;Silva et al, 2022). A pesar de ser una opción que ofrece resultados prometedores en cuanto a producción, el problema radica en las condiciones adversas económicamente hablando de los pequeños productores de vainilla, ya que carecen de la infraestructura necesaria y de los fondos necesarios para el establecimiento de biofábricas.…”
Section: Características Del Cultivo Y Producción De Vanilla Planifoliaunclassified